Prevalence of Vitamin D Insufficiency in Patients with Dry Eye Disease - Samar Fatima, Maeirah Shafique, Beenish Saleem, Nauroz Fatima, Bushra Akbar, Noureen Malik, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Dry Eye Disease (DED) is a complex ocular condition which, due to its various factors, is capable of causing visual impairment and diminish an individual’s quality of life. Among the many potential factors included, DED is vitamin D deficiency. The following investigation focused on the extent of vit D₃ deficiency, its prevalence, severity in association with DED. Methods: This prospective cross-sectional hospital-based study was conducted at Tertiary care hospital, Murree, from June 2022 to June 2023. I enrolled 375 participants through non-probability consecutive sampling (200 with DED, 175 controls). All participants filled the Ocular Surface Disease Index (OSDI), and underwent Schirmer’s I Test and Tear Break-Up Time (TBUT). For Serum 25-hydroxyvitamin D [25(OH)D] levels, measurements were done using ELISA. For analysis, I used SPSS v25.0. You used independent t-tests for comparing continuous variables, while chi-square tests with Cramer’s V were used for analyzing categorical data. I considered a p < 0.05 as statistically significant. Results: Mean serum vitamin D₃ concentrations were considerably lower in DED patients compared to the control group (21.5 ± 7.6 ng/ml vs. 34.4 ± 7.8 ng/ml; t(373) = -16.20, p < 0.001). DED patients also had a increased prevalence of deficiency of vitamin D (69.0%) compared to the controls (36.6%) which was statistically significant. Higher OSDI severity was linked to a greater prevalence of vitamin D deficiency, χ²(6) = 113.7, p < 0.001, Cramer’s V = 0.389. Conclusion: Patients with dry eye should examine their vitamin D levels since low vitamin D₃ may be linked to the development and severity of eye issues. Keywords: Dry eye disease, Vitamin D₃ deficiency, Schirmer’s test, TBUT